The effect of sustainable agriculture programs on chemical fertilizer consumption patterns in farmers - Jaimini Sarkar; Chiradeep Sarkar (Multidisciplinary Adaptive Climate Insights, 2024)
Background- Fertilizers are essential to enhancing food security by enhancing crop growth. The selection of chemical fertilizers over organic fertilizers brings environmental consequences. The government is trying to achieve food security and promote organic fertilizers over chemical fertilizers by implementing various programs. Aim- The study is carried out to understand the effect of government policies on farmers' chemical fertilizer consumption patterns. Design- The data of fifteen years’ chemical fertilizer consumption was divided in three sub-groups. Statistical analysis was done to understand the trend of chemical fertilizer consumption of the farmers. Results- The analysis of data clearly shows the steadily increasing pattern of chemical fertilizer consumption. Conclusions- The study clearly shows there is no effect of sustainable agriculture policies framed by the government on the consumption of chemical fertilizers by farmers. Across the study period, farmers were inclined to use chemical fertilizers, related to a lack of awareness of the principles of appropriate fertilizer management that can limit environmental damage.